2012
DOI: 10.3109/08941939.2011.618523
|View full text |Cite
|
Sign up to set email alerts
|

miR-17-5p as a Novel Prognostic Marker for Hepatocellular Carcinoma

Abstract: miR-17-5p is highly elevated in HCC, especially in HCC with metastasis. miR-17-5p can serve as a novel prognostic marker for HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 31 publications
3
38
0
Order By: Relevance
“…This miRNA was reported up-regulated in HCC and a novel biomarker in a recently published study [31]. Our finding is also in agreement with this study.…”
Section: Discussionsupporting
confidence: 95%
“…This miRNA was reported up-regulated in HCC and a novel biomarker in a recently published study [31]. Our finding is also in agreement with this study.…”
Section: Discussionsupporting
confidence: 95%
“…But on the other hand, it contradicts other studies that reported reduced IGFBP-3 mRNA expression and protein levels in metastatic HCC patients [12,13] . Moreover, the repression of miR-17-5p in HCC tissues ( Figure 1A) corroborates our previous results that showed a significant downregulation of miR-17-5p expression in non-metasatic HCC patients [20] , but nonetheless it contradicts other studies in metastatic HCC tissues [23] . These disparities can, however, be attributed to differences in the cohorts of patients included in the various studies, with regards to stage and etiology of the disease as well as other factors such as ethnicity, gender and age.…”
Section: Discussionsupporting
confidence: 71%
“…In tissues, with regard to up-regulated microRNAs in HCC tissues, highly expression of miR-106b-5p, miR-155-5p, miR-17-5p, miR-182-5p, miR-183-5p, miR-18b-5p, miR-21-5p, miR-25-3p, miR-331-3p, miR-9-5p and miR-96-5p were significantly correlated with invasion and metastasis454752566465666768697071. The expression level of miR-1269a in HCC patients without portal vein tumor embolus was reduced72.…”
Section: Resultsmentioning
confidence: 99%